2005
DOI: 10.1002/ajmg.a.30739
|View full text |Cite
|
Sign up to set email alerts
|

Are the betaine‐homocysteine methyltransferase (BHMT and BHMT2) genes risk factors for spina bifida and orofacial clefts?

Abstract: Abnormalities in folate and/or homocysteine metabolism may adversely influence embryonic development, leading to the birth of infants with a variety of congenital malformations, including neural tube defects (NTDs) and craniofacial abnormalities. Based upon suggestive evidence that periconceptional folic acid supplementation is effective in preventing a significant proportion of the aforementioned birth defects, genetic variation in the folate biosynthetic pathways may influence the infant's susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 25 publications
0
24
2
Order By: Relevance
“…(50,51) and spina bifida (52) associated with Gln/Gln versus Arg/Arg at BHMT codon 239 have been suggested among three previous studies. However, another study observed no association with spina bifida (53), and Arg 239 Gln has not been associated with altered BHMT activity (51) or homocysteine levels (50). Although the evidence for an association between BHMT Arg 239 Gln and homocysteine-related diseases is weak, the suggested reduced risks of cardiovascular disease and spina bifida is in contrast to the increased risk of colorectal cancer due to the Gln allele that we observed.…”
Section: Resultscontrasting
confidence: 73%
“…(50,51) and spina bifida (52) associated with Gln/Gln versus Arg/Arg at BHMT codon 239 have been suggested among three previous studies. However, another study observed no association with spina bifida (53), and Arg 239 Gln has not been associated with altered BHMT activity (51) or homocysteine levels (50). Although the evidence for an association between BHMT Arg 239 Gln and homocysteine-related diseases is weak, the suggested reduced risks of cardiovascular disease and spina bifida is in contrast to the increased risk of colorectal cancer due to the Gln allele that we observed.…”
Section: Resultscontrasting
confidence: 73%
“…One common variant in the BHMT gene, A742G, has been identified; however, two independent studies failed to detect a significant association with NTD risk (Morin et al, 2003b;Zhu et al, 2005). The BHMT A742G SNP has not shown a strong relationship with homocysteine levels (Weisberg et al, 2003;Ananth et al, 2007), indicating that it may not have functional relevance.…”
Section: Genes Within the Methionine/homocysteine Metabolic Cyclementioning
confidence: 93%
“…BHMT c.716G>A was found not to be related to plasma tHcy concentration (Fredriksen et al 2007;Heil et al 2000;Morin et al 2003;Weisberg et al 2003), but a recent large epidemiological study demonstrated decrease in dimethylglycine (the product of the BHMT reaction) according to the number of c.716A alleles (Fredriksen et al 2007), suggesting that this polymorphism may have metabolic effects. The variant c.716A allele has been associated with increased risk (Morin et al 2003), decreased risk (Boyles et al 2006), or no change in risk (Zhu et al 2005) of spina bifida, and decreased risk of coronary artery disease and no association with risk of cardiovascular disease (Heil et al 2000) or aortic aneurysm (Giusti et al 2008). Furthermore, carriers of the variant allele have been reported to have increased risk of colorectal cancer (Koushik et al 2006) and possibly decreased risk of colorectal adenoma when combined with high methyl status (Hazra et al 2007).…”
Section: Common Polymorphism In the Bhmt Gene And Disease Riskmentioning
confidence: 94%